Concentration of Cu(II) and Cd(II) from natural river water by Adsorption on a Modified Silica Surface - Ferreira, Guilherme [UNESP]; Pereira, Adriano S. [UNESP]; Caetano, Laercio [UNESP]; Santos, Ademir dos [UNESP]; Martines, Marco Antonio U.; Padilha, Pedro M. [UNESP]; Zara, Luiz Fabricio; Silva, Rafael I. V. [UNESP]; Castro, Gustavo R. [UNESP] (My University, 2010)
A high surface area silica gel (737 ± m2 g-1) was synthesized modified through a two-step reaction with a 4-amino-2-mercaptopyrimidine ligand and applied to Cu(II) and Cd(II) adsorption from an aqueous medium. The modified material was characterized by FTIR, which showed that attachment of the molecule occurred via thiol groups at 2547 and 2600 cm-1, and by elemental analysis that indicated the presence of 0.0102 mmol of ligand. The data from adsorption experiments were adjusted to a modified Langmuir equation and the maximum adsorption capacity was 6.6 and 3.8 μmol g-1 for Cu(II) and Cd(II), respectively. After adjusting several parameters, the material was applied in the preconcentration of natural river water using a continuous flow system before and after sample mineralization, and the results showed a 10-fold enrichment factor. The proposed method was validated through preconcentration and analysis of certified standard reference material (1643e), whose results were in agreement with the values provided by the manufacturer.
Keywords: Continuous flow system; Metal ions; Preconcentration; River water; Solid phase extraction; Surface modification